Innovative and conventional "conservative" technologies for the treatment of uterine fibroids in Italy: A multidimensional assessment - L. Ferrario; E. Garagiola; C. Gerardi; G. Bellavia; S. Colombo; C. Ticca; C. Rossetti; M. Ciboldi; M. Meroni; A. Vanzulli; A. Rampoldi; T. Bignardi; et al. (Health Economics Review, 2022)
Background: To evaluate the potential benefits of the Magnetic Resonance-guided high intensity Focused Ultrasound (MRgFUS) introduction in the clinical practice, for the treatment of uterine fibroids, in comparison with the standard "conservative" procedures, devoted to women who wish to preserve their uterus or enhance fertility: myomectomy and uterine artery embolization (UAE). Methods: A Health Technology Assessment was conducted, assuming the payer's perspective (Italian National Healthcare Service). The nine EUnetHTA Core Model dimensions were deeply investigated, by means of i) a literature review; ii) the implementation of health economics tools (useful for uterine fibroids patients' clinical pathway economic evaluation, and budget impact analysis), to define MRgFUS economic and organizational sustainability, and iii) administration of specific questionnaires filled by uterine fibroids' experts, to gather their perceptions on the three possible conservative approaches (MRgFUS, UAE and myomectomy). Results: Literature revealed that MRgFUS would generate several benefits, from a safety and an efficacy profile, with significant improvement in symptoms relief. Advantages emerged concerning the patients' perspective, thus leading to a decrease both in the length of hospital stay (p-value< 0.001), and in patients' productivity loss (p-value = 0.024). From an economic point of view, the Italian NHS would present an economic saving of - 6.42%. A positive organizational and equity impact emerged regarding the capability to treat a larger number of women, thus performing, on average, 131.852 additional DRGs. Conclusions: Results suggest that MRgFUS could be considered an advantageous technological alternative to adopt within the target population affected by uterine fibroids, demonstrating its economic and organisational feasibility and sustainability, with consequent social benefits.
Keywords: 330; Decision support techniques; Economic evaluation; Magnetic resonance imaging/methods; Technology assessment; Ultrasound therapy/methods